Predictive influence of intrapersonal and environmental factors on the psychosocial adjustment of adolescents with post-lingual hearing loss (2017)
Adolescence is characterized by rapid physiological, psychological, and social development which presents considerable challenge when joined with the burden of acquired hearing loss. This study adopted a descriptive survey research design of expost-facto type. Three instruments; Nottingham Adjustment Scale, Hunter Opinions and Personal Expectations Scale and structured interview questionnaire were used to answer the three research questions raised. It focused on influence of intrapersonal and environmental factors on the psychosocial adjustment of adolescents with post- lingual hearing loss in Osun State. Data were analyzed using percentages, Pearson’s correlation and regression analysis. Psychosocial adjustment has a correlation with intrapersonal factors (r=0.44, p<0.05) and environmental factors (r=0.47, p<0.05). Intrapersonal and environmental factors showed significantly joint prediction of psychosocial adjustment of adolescents with post-lingual hearing loss. (F (2, 47) = 13.09; R = 0.60; R2 = 0.33; p<.05). Also, interpersonal factors (B=0.47; t = 3.17; p<.05) and environmental factors (B=0.44; t = 0.41; p<.05) revealed significantly independent prediction of psychosocial adjustment of adolescents with post-lingual hearing loss and environmental factors contributed more to the explained variation (fi = 0.41) than intrapersonal factors (B = 0.38). Understanding the process of adjusting to acquired hearing loss and the sequelae of such a loss should be the first step in developing and implementing appropriate intervention strategies to facilitate adaptation to the loss. Orientation should be given through different media available to educate the society about hearing loss, causes, prevention and management of people with hearing loss, as well as the ills of discriminating against those with hearing loss. Efforts must be made to improve the psychosocial adjustment of individuals with post-lingual hearing loss in this age group.